If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + b) = 42 (7 * 2 + b * 2) = 42 (14 + 2b) = 42 Solving 14 + 2b = 42 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2b = 42 + -14 Combine like terms: 14 + -14 = 0 0 + 2b = 42 + -14 2b = 42 + -14 Combine like terms: 42 + -14 = 28 2b = 28 Divide each side by '2'. b = 14 Simplifying b = 14
| Y=ln(x+1)+4 | | 3(7+B)=90 | | -7(1+2m)=-5(2m-5) | | 5/3/4/5+3/2x2/3 | | 13x+21=4x+12 | | -5a-6(1-5a)=2-(2a+8) | | x^2-2x+12=3x+36 | | -36x^2+144x-60=0 | | (m-15)(m+9)=m-15 | | -(5+3p)-6p=-4(p+2)-7 | | (y-8)(y+2)=y-8 | | 0.4/a=0.32 | | 7x-8=3x-40 | | 3a+(a+b)=180 | | a+3a+(a+b)=180 | | 1.5(x-1)-1.5=2.5(x-3) | | -8(4n+8)-2(1-3n)=-n+8+n+4 | | -2+2(6)= | | -4r+8=32 | | -3p+3p=-6(5p+1)+6(3+7p) | | -4.8/-1.6 | | -5(6p+8)+6(p-7)= | | -7/8x=-21/32 | | 4q-3.3=2.4q+10.78 | | 7(2x+3)+8=-6(7x+4)+3x | | -2x+6x-3= | | (-4t+8)(4t+1)=0 | | -5X+6/5=9X+7/2 | | 3x-5y=19 | | 180-x=2x+12 | | 3(2x+3)=-2x+2 | | 7(x-12)-11=22x-275 |